Gemcitabine-induced gouty arthritis attacks. (September 2013) - Bottiglieri, Sal; Tierson, Neil; Patel, Raina; Mo, Jae-Hyun; Mehdi, Syed
In this case report, we review the experience of a patient who presented with early stage pancreatic cancer (Stage IIb) who underwent a Whipple procedure and adjuvant chemoradiation. The patient's past medical history included early stage colon cancer in remission, post-traumatic-stress-disorder, hypertension, hyperlipidemia, osteoarthritis, gout, and pre-diabetes. Chemotherapy initially consisted of weekly gemcitabine. The patient developed acute gouty attacks after his second dose of gemcitabine, which brought him to the emergency room for emergent treatment on several occasions. Gemcitabine was held and treatment began with fluorouracil and concurrent radiation. After completion of his chemoradiation with fluorouracil, he was again treated with weekly gemcitabine alone. As soon as the patient started gemcitabine chemotherapy the patient developed gouty arthritis again, requiring discontinuation of chemotherapy. The patient received no additional treatment until his recent recurrence 8 months later where gemcitabine chemotherapy was again introduced with prophylactic medications consisting of allopurinol 100 mg by mouth daily and colchicine 0.6 mg by mouth daily throughout gemcitabine chemotherapy, and no signs of gouty arthritis occurred. To our knowledge, this is the first case report describing gout attacks associated with gemcitabine therapy. There is limited data available describing the mechanism that gouty arthritis may be precipitated from gemcitabine chemotherapy. Further monitoring and management may be required in patients receiving gemcitabine chemotherapy with underlying gout.